Implementation of SIAPIK for Preparing MSME Financial Statements (Case Study on The Ri.ch Event Organizer) - Sumaraw, Marcelo; Sutanto, Cindy; Dalisang, Archelia Avril Margareth; Ni Made Devi Artani; Tuerah, Raykes Hinrich (Journal of Applied Accounting, 2025)
Financial statements are very important for all businesses, including MSMEs, because they can be used by MSME actors or lenders to analyze the condition of a business. However, many have not prepared them in accordance with SAK EMKM and without using applications due to limited knowledge or capability. The researcher selected The Ri.ch Wedding and Event Organizer as the research object. This study aims to develop accounting policies, classify transactions, and prepare financial statements in accordance with SAK EMKM through the implementation of SIAPIK. This research applies a qualitative approach with data obtained from interviews, observations, and documentation. The data consist of an overview of the business, business processes, and financial transactions. Data analysis produced accounting policies, transaction classifications, and the application of SIAPIK-based financial statements. The study on The Ri.ch Wedding and Event Organizer found that this business has not yet used financial applications and SAK EMKM, which caused difficulties in bookkeeping. SIAPIK is offered as a practical solution with the implementation of SAK EMKM as the basis for its preparation. With this research, MSME actors can understand how to prepare financial statements easily, quickly, and in a standardized way, which can then be used by stakeholders in decision-making. Keywords: MSMEs, Business Processes and Financial Transactions, Financial Statements, SIAPIK, SAK EMKM